Nanopore Sequencing and Bioinformatics for Rapidly Identifying Cultural Heritage Spoilage Microorganisms - Grottoli, Alessandro; Beccaccioli, Marzia; Zoppis, Emma; Fratini, Rosita Silvana; Schifano, Emily; Santarelli, Maria Laura; Uccelletti, Daniela; Reverberi, Massimo (Frontiers in Materials, 2020)
Microbiological methodologies allow understanding the causes that lead to the development of a certain microbial community colonizing an artistic surface, to characterize its composition and describe its role in the deterioration of the constituent materials. Metagenomics allows identifying microbial communities directly in their natural environments, bypassing the need for isolation and cultivation of individual species, thus providing a more comprehensive picture of the biodiversity present on a surface compared with standard cultivation methods. Furthermore, molecular analyses require small amounts of material, favoring the preservation of the artistic surface during sampling. Here, we verified the suitability of a protocol consisting in DNA extraction with micro-invasive sampling, using adhesive tape, PCR amplification with universal primers [bacteria (16S), fungi (ITS), and Viridiplantae (18S)], and amplicon sequencing by Oxford Nanopore Technologies (ONT) in the hypogeum of Basilica di San Nicola in Carcere Church (Rome, Italy). Sequence data were analyzed with a bioinformatic pipeline customized for pinpointing cultural heritage spoiling organisms, named “AmpLIcon SequencIng Analysis” (ALISIA). These data were integrated with traditional microbiology techniques that allowed the isolation of cultivable bacteria; three species were also characterized through their capability of biofilm formation and antibiotic resistance. Further, Fourier-transform infrared spectroscopy (FTIR) spectroscopy was performed to characterize the main products present on the masonry surface providing indications on the type of decay present. This novel biological workflow represents a powerful opportunity to investigate the microbial colonization of artistic surfaces aimed at implementing preservation strategies of cultural heritage from bio-spoilage.